Marketing, advertising and consumer law on the subject alcoholic beverages - Burga Solar, Manuel (2015)
Is eminently important legislative recognition that establishes the normative framework respect to the regulation of marketing, consumption and advertising of alcoholic beverages in our country. Indeed, the theme to develop is regulated by the Law Regula Marketing, Consumption and Advertising Alcoholic Beverage Law N° 28681 and S.D. N° 012-2009-SA approved the Regulations of the referred law.